Volleyball Smash Practice Development Model - Siti Ayu Risma Putri; Mutiara Fajar; Dede Dwiansyah Putra (Universitas PGRI Palembang, 2023)
This study aims to develop basic volleyball smash techniques, a book product that will be produced in this research. The objective of this research is for some coaches to implement training programs in their respective clubs. The method used in this research is development research (R&D). The steps in compiling this research are excerpts from Borg and Gall's research steps where there are 10 steps, but because Indonesia is currently experiencing the Covid-19 pandemic, this study only uses the third step of Borg and Gall's research. This study used a validity test of the volleyball smash training model which was carried out by 3 experts, namely coaching experts, volleyball experts, and media experts. The instrument used to collect data about the volleyball smash feasibility test is using a questionnaire or questionnaire with a research scale. Evaluation data uses qualitative and quantitative descriptive percentages. The results show that the PGRI Palembang University volleyball club smash training model is feasible to apply